2007
DOI: 10.1529/biophysj.106.101410
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model of Electrotonic Interactions between Ventricular Myocytes and Fibroblasts

Abstract: Functional intercellular coupling has been demonstrated among networks of cardiac fibroblasts, as well as between fibroblasts and atrial or ventricular myocytes. In this study, the consequences of these interactions were examined by implementing the ten Tusscher model of the human ventricular action potential, and coupling it to our electrophysiological models for mammalian ventricular fibroblasts. Our simulations reveal significant electrophysiological consequences of coupling between 1 and 4 fibroblasts to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
351
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(381 citation statements)
references
References 43 publications
29
351
1
Order By: Relevance
“…The elastic modulus rises from (18±2) kPa in the normal heart muscle of non-infarcted animals to (55±15) kPa in significant fibroblast proliferous muscle of infarcted animals, an almost three-fold increase (Berry et al, 2006). Therefore, the functional roles of the fibroblasts in cardiac electrical and mechanical activities have attracted increasing interest, and have been explored in experimental studies (Miragoli et al, 2007;Zlochiver et al, 2008) and computational models (MacCannell et al, 2007;Tanaka et al, 2007;Jacquemet and Henriquez, 2008;Zlochiver et al, 2008;Sachse et al, 2009). Both experimental and computational studies (Miragoli et al, 2006;Jacquemet and Henriquez, 2008;Zlochiver et al, 2008) have illustrated that non-monotonic changes in conduction velocity (CV) are caused by increasing the fibroblast population.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The elastic modulus rises from (18±2) kPa in the normal heart muscle of non-infarcted animals to (55±15) kPa in significant fibroblast proliferous muscle of infarcted animals, an almost three-fold increase (Berry et al, 2006). Therefore, the functional roles of the fibroblasts in cardiac electrical and mechanical activities have attracted increasing interest, and have been explored in experimental studies (Miragoli et al, 2007;Zlochiver et al, 2008) and computational models (MacCannell et al, 2007;Tanaka et al, 2007;Jacquemet and Henriquez, 2008;Zlochiver et al, 2008;Sachse et al, 2009). Both experimental and computational studies (Miragoli et al, 2006;Jacquemet and Henriquez, 2008;Zlochiver et al, 2008) have illustrated that non-monotonic changes in conduction velocity (CV) are caused by increasing the fibroblast population.…”
Section: Introductionmentioning
confidence: 99%
“…ten Tusscher and Panfilov (2007) showed that CV decreased from 0.7 to 0.3 m/s as the percentage of fibroblast proliferous cells rose from 0 to 40% in two-dimensional (2D) tissue. In simulation studies, it was reported that myocyte-fibroblast coupling modulated AP morphology (MacCannell et al, 2007;Jacquemet and Henriquez, 2008;Sachse et al, 2009). Coupling two or four fibroblasts to a ventricular myocyte resulted in a decrease in action potential duration (APD) from a control value of 263 ms to 195 or 155 ms, respectively (MacCannell et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fibroblasts are modelled as passive cells; for these fibroblasts, we use the model given by MacCannell, et al [10].…”
Section: Methodsmentioning
confidence: 99%